Integrasi Learning Management System (LMS) dan Pendekatan Deep Learning dalam Pendidikan Agama Islam di SMK Negeri 1 Langgudu - Sunardin; Agussalam; Ferdiansyah (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to describe the implementation of Islamic Religious Education using a Learning Management System (LMS) integrated with a deep learning approach and to analyze its impact on students’ active participation, conceptual understanding, engagement, and motivation to learn. This study employs a qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that the integration of LMS and deep learning fosters more active, interactive, and meaningful learning. Student engagement increases through participation in online discussions and the willingness to express opinions, while conceptual understanding develops through the ability to connect course material to real-life situations and the analysis of case studies. Furthermore, student engagement and learning motivation also improved, as evidenced by independent access to the LMS, active participation, and enthusiasm in following the lessons. In conclusion, the integration of the LMS and the deep learning approach has a positive impact on the quality of the Islamic Education learning process at SMK 1 Langgudu.